The Effect of Lavender Aromatherapy on Nausea and Vomiting in Pregnant Women in First Trimester of Pregnancy - Sagitarini, Putu Noviana; Darmawati, I Dewa Ayu Agra; Agustini, Ni Komang Tri; Sari, Ni Made Candra Citra (Babali Nursing Research, 2025)
Background: One of these discomforts that occurs in the first trimester is nausea and vomiting. It’s occurs continuously without proper treatment can interfere with the mother's activities. One of the managements to reduce emesis gravidarum non-pharmacologically is administering lavender aromatherapy. The purpose of this study was to determine the effect of administering lavender aromatherapy to nausea and vomiting in pregnant women in their first trimester. Methods: The type of this research was a pre-experimental design using one group pre-test and post-test design. The research location was in Serangan Village, South Denpasar III Public Health Center Work Area. The sampling method was consecutive sampling. The study involved 24 respondents. The data collection instruments used were the Numeric Rating Scale for measuring nausea and vomiting, and the SOP for administering lavender aromatherapy. The data analysis utilized univariate analysis and bivariate analysis using Wilcoxon Rank Test. Results: Most of the respondents before being administered with lavender aromatherapy experienced nausea and vomiting in the moderate category, namely 79.2%. After lavender aromatherapy administration, it was found about 62.5%. pregnant women had a mild nausea and vomiting category. There was a difference in the score of nausea and vomiting in the first trimester of pregnant women before and after being administered with lavender aromatherapy with a p-value = 0.000. Conclusion: The administration of lavender aromatherapy can reduce nausea and vomiting in pregnant women. Health workers can consider using lavender aromatherapy as a complementary therapy in treating nausea and vomiting in pregnant women in the first trimester.